Potential predictors of nipple trauma from an in-home breastfeeding programme: A cross-sectional study. Issue 4 (August 2016) - Thompson, Robyn; Kruske, Sue; Barclay, Lesley; Linden, Karin; Gao, Yu; Kildea, Sue
Abstract: Background: Australian breastfeeding rates fall significantly in the months following birth, often as a result of breastfeeding complications. Aim: To explore the potential risk factors for nipple trauma and breast engorgement in a group of women who were referred to the in home breastfeeding service in Melbourne, Australia. Method: A retrospective, cross-sectional analyses of the maternal–infant records ( n  = 653) from 2003 to 2007 including demographic characteristics; pregnancy, labour and birth data; the presenting complications and observational and diagnostic results. Bivariate and logistic regression analyses were conducted to explore the predictors of nipple trauma and engorgement. Results: Nipple trauma was the most common presenting complication (62.9%). Logistic regression analyses identified four statistically significant predictors: facio-mandibular asymmetry (AOR 4.21, 95% CI [1.25–14.20]), inflammatory mastitis (AOR 2.99, 95% CI [1.57–5.68], nipple malignment (AOR 2.51, 95% CI [1.13–5.55]) and the cross-cradle technique (AOR 1.90, 95% CI [1.03–3.50]). Engorgement was associated with the first postpartum breastfeed being less than one-hour duration (AOR 2.01, 95% CI [1.07–3.79]). Conclusion: Nipple trauma was associated with commonly taught techniques that involved the cross-cradle hold and manoeuvres of the breast, nipple and baby that resulted in nipple malalignment and facio-mandibular asymmetry. This practice, appeared to interfere with the baby's intra-oral function by restricting movement of the cranio-cervical spine and nuchal ligament. The combination appeared to limit the baby's instinctive ability to activate neuro-sensory mammalian behaviours to freely locate and effectively draw the nipple and breast tissue without causing trauma. Changes to the first and early breastfeeding techniques are recommended.